The correlation between second-hand tobacco smoke exposure and biofilm formation in chronic rhinosinusitis - Arkadiusz Standyło; Aleksandra Obuchowska; Grażyna Mielnik-Niedzielska (Kazimierz Wielki University, 2022)
Introduction and purpose Tobacco smoke is a major health concern globally. Due to tobacco epidemic, approximately 8 million people died as a result of cigarette smoking in 2020 alone, where 1.2 million were caused by non-smokers inhaling second-hand smoke. Chronic rhinosinusitis (CRS) is an inflammatory condition that has a significant health and  economic impact worldwide. Despite its great burden on the health-care system and patients' quality of life, the variety of therapy options for CRS is currently limited. Tobacco-induced biofilm formation may contribute to the refractory nature of many respiratory diseases reported in smokers and second-hand smokers, due to increased resistance to antibiotics. The aim of this study is to present that exposure to household passive smoking may induce the formation of nasal biofilms. Brief description of the state of knowledge             Chronic bacterial infections involving biofilms have recently been recognised as a factor in CRS pathogenesis. The presence of biofilms on the mucosa of CRS patients is associated with more severe pre-operative disease, persistent postoperative symptoms, ongoing mucosal inflammation, and infections following endoscopic sinus surgery. Tobacco smoke and CRS have been associated because of the immunosuppressive and irritating effects of tobacco smoke on sinonasal epithelial cells. Smoking uptake and cessation have been shown to affect microbial communities, with smokers having not just distinct microbial communities, but also a higher frequency of possible pathogens in those communities. Summary             Biofilms may play a significant role in the development of chronic rhinosinusitis. The impact of tobacco smoke on biofilm development could have major implications not only for CRS but also for other respiratory infections.